Perancangan Portal Online Course Untuk Menjadi Penulis Buku Dan Ilustrator Studi Kasus Bersamaadya.Com - Oktaviarini, I Gusti Ayu Putu Gita (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Technological developments have encouraged the emergence of new learning methods through online courses, which allow learning to take place anytime and anywhere. In Indonesia, interest in writing and illustration is increasing, marked by the emergence of many new writers and illustrators due to the ease of publishing digital and printed works. However, there is no dedicated platform that can accommodate and support the development of creativity in these fields. To address this need, BersamaAdya.com, through the Adya Foundation, designed an online course platform focused on literacy, with the aim of providing access to relevant learning and guidance from experienced mentors so that aspiring writers and illustrators are able to produce creative works worthy of the industry. The system was designed using a prototype method through the stages of UML, ERD, and Low and High Fidelity design, then tested using the System Usability Scale (SUS) method. The test results showed an average score of 77.97, which falls into the Good, Grade C, and Acceptable categories, so the system is considered feasible and has the potential to become a platform for the development of writers and illustrators.